Towards climate neutrality: economic impacts, opportunities and risks: Report of Abstracts - Latvijas Universitāte. 80. starptautiskā zinātniskā konference (Latvijas Universitāte. 80.starptautiskā zinātniskā konference, 2022)
The conference session aims to provide a platform/opportunity for scholars, researchers and professionals from different disciplinary backgrounds to meet, exchange ideas, findings, research results and discuss the topical issues related to climate neutrality.
Keywords: Research Subject Categories::SOCIAL SCIENCES::Business and economics; CSR; Climate Policy; Energy development; Energy policy